Tracking the water fingerprints of Cocos Island: a stable isotope analysis of precipitation, surface water, and groundwater - Corrales, José L.; Sánchez-Murillo, Ricardo; Esquivel-Hernández, Germain; Herrera, Esteban; Boll, Jan (Revista de Biología Tropical, 2016)
The use of stable isotopes of water, both δ2H and δ18O has provided novel insights in hydrological studies, ecological applications, understanding climate variability, and reconstructing paleoclimate. However, information on the stable isotope composition of water in tropical marine island environments is normally scarce within the Central America Isthmus. Here, we present the first isotopic characterization of precipitation, surface water, and groundwater at Cocos Island, Costa Rica within the eastern tropical Pacific Ocean region. Our results show that the Cocos Island MWL can be described as: δ2H=8.39·δ18O+13.3; r2=0.98 (n=29). Dry season rainfall events ranged from -4.9 ‰ δ18O up to -2.4 ‰ δ18O with a mean d-excess of 13.2 ‰. By the beginning of May, the Intertropical Convergence Zone reaches Costa Rica resulting in a notable depletion in isotope ratios (up to -10.4 ‰ δ18O and -76.2 ‰ δ2H). During the wet season, δ18O composition averaged -6.1 ‰ δ18O and -38.5 ‰ δ2H with a mean d-excess of 9.9 ‰. HYSPLIT air mass back trajectories indicate a strong influence on the origin of precipitation of two main moisture transport mechanisms, the northeasterly (January-May) and southwesterly (May-November) trade winds. Small seasonal variations were observed in the isotopic composition of surface water throughout the year with mean values ranging from -3.9 ‰ δ18O (dry season, n=19) up to -4.8 ‰ δ18O (wet season, n=13). Groundwater samples exhibited a similar trend with more depleted composition during the wet season (-5.2 ‰ δ18O and -29.8 ‰ δ2H). Overall, the marine isotopic composition measured in meteoric water at Cocos Island serves to better delineate the isotopic contribution of Pacific moisture towards the Central America Isthmus. It also provides a valuable isotopic reference to discriminate from orographic distillation and Caribbean enriched rainfall inputs in continental studies.